2018
DOI: 10.1016/j.jmb.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Soft Interactions with Model Crowders and Non-canonical Interactions with Cellular Proteins Stabilize RNA Folding

Abstract: Living cells contain diverse biopolymers, creating a heterogeneous crowding environment, the impact of which on RNA folding is poorly understood. Here, we have used single-molecule fluorescence resonance energy transfer to monitor tertiary structure formation of the hairpin ribozyme as a model to probe the effects of polyethylene glycol and yeast cell extract as crowding agents. As expected, polyethylene glycol stabilizes the docked, catalytically active state of the ribozyme, in part through excluded volume e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…It is becoming increasingly clear that excluded volume effects mediated by molecular crowding affect macromolecular structure, protein stability, enzyme activity and nucleo-cytoplasmic organization (Daher et al, 2018;Delarue et al, 2018;Hancock, 2004;Minton, 2001;Sukenik et al, 2018). Previous work has noted the potential for phase separation to dynamically buffer the intracellular protein concentration (Alberti et al, 2019).…”
Section: The Features and Functional Consequences Of Widespread Intramentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming increasingly clear that excluded volume effects mediated by molecular crowding affect macromolecular structure, protein stability, enzyme activity and nucleo-cytoplasmic organization (Daher et al, 2018;Delarue et al, 2018;Hancock, 2004;Minton, 2001;Sukenik et al, 2018). Previous work has noted the potential for phase separation to dynamically buffer the intracellular protein concentration (Alberti et al, 2019).…”
Section: The Features and Functional Consequences Of Widespread Intramentioning
confidence: 99%
“…Yet, the significance of the propensity of these biomolecules to phase-separate under the physiological conditions of their native intracellular environment, where molecular crowding is dominant, is poorly understood (Alberti et al, 2019). While it is possible to alter crowding within the test tube via the addition of synthetic macromolecules (Alberti et al, 2019), the nature and extent of crowding in the cellular context is quite different (Daher et al, 2018;Walter, 2019) and dynamically changes with the cellular state. For example, cell volume adjustments occur during processes critical to both cellular homeostasis and pathology, including the cell cycle (Tzur et al, 2009;Zlotek-Zlotkiewicz et al, 2015) as well as upon cell adhesion and migration (Guo et al, 2017;Watkins and Sontheimer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The predicted significant impact of a large number of low‐affinity competitors on specific binding interactions is the reality of the cell's crowded molecular environment (Figure C). In fact, increasing evidence is emerging that, for example, many cryptic RNA‐binding sites exist on proteins of all trades, including many metabolic housekeeping enzymes . Similarly, such dynamic equilibrium considerations are the essence of recent modeling efforts of the regulatory RNA silencing machinery, whereby each RNA target competes both for protein partners of the RNA‐induced silencing complex (RISC) and microRNAs (miRNAs; Figure ) .…”
Section: The Cell's Reality Is Diversely Crowdedmentioning
confidence: 99%
“…Yet, even well‐studied metabolic pathways have to be amended and expanded regularly, with important implications for normal physiology and diseases such as cancer . Similarly, recent studies have found that hundreds of proteins and RNAs “moonlight,” in that they each participate in multiple distinct biochemical pathways by using different parts of their surfaces to interact with diverse binding partners . When even metabolic enzymes that are thought to “normally” phosphorylate small metabolites equally function as protein kinases and phosphorylate a variety of protein substrates to regulate fundamental cellular functions, it is no wonder that cellular networks show much more redundancy and plasticity, and are harder to therapeutically target, than expected from simple linear cause‐and‐effect relationships.…”
Section: The Cell's Reality Is Diversely Crowdedmentioning
confidence: 99%
“…Daher and coworkers investigated the effect of crowding agents on the docking-undocking equilibrium of the hairpin ribozyme [24]. Two crowding agents are examined, polyethylene glycol and yeast extract.…”
mentioning
confidence: 99%